Cost-effective analysis of unilateral cochlear implantation under the Taiwan national healthcare insurance. (2nd January 2020) - Fang, Te-Yung; Cheng, Li-Jen; Wu, David Bin-Chia; Wang, Pa-Chun
Abstract: Objective: The value of cochlear implantation (CI) has not been established in Taiwan. The purpose of this study was to evaluate the cost-effectiveness of paediatric CI within the context of Taiwan's national health insurance (NHI) programme. Design: A Markov model-based cost-utility analysis (CUA) was conducted to evaluate the cost-effectiveness of a unilateral CI (UCI) with a contralateral acoustic hearing aid (UCI-HA) compared with a bilateral HA. We performed one-way sensitivity analyses to identify the cost variables that affected the incremental cost-effectiveness ratio (ICER) the most. Monte Carlo simulation was used to explore the simultaneous effect of all uncertain parameters on cost-effectiveness. Study sample: Not applicable. Results: Compared with bilateral HAs, the ICER for UCI-HA was 6487 per quality-adjusted life year (QALY) gained. The ICERs were consistently below 7000 per QALY gained and were most sensitive to the selling price of the external CI device. When this selling price increased by 10%, the ICER of UCI-HA would increase to 6954 per QALY gained. UCI-HA has a probability greater than 50% of being cost-effective if the cost-effectiveness threshold exceeds approximately 10, 000 per QALY. Conclusions: Our analysis suggested that within the context of Taiwan's NHI programme, UCI is highly cost-effective for deaf children.